Probing the magnetoelectric effect in noncentrosymmetric superconductors by equal-spin Andreev tunneling. (19th December 2018) - Tkachov, G
Abstract: In noncentrosymmetric superconductors (NCSs), the conversion of a charge current into spin magnetization—the so called magnetoelectric effect—is the direct indicator of the unconventional, mixed-parity order parameter. This paper proposes a scheme to detect the magnetoelectric effect by anomalous, equal-spin Andreev tunneling in NCS/ferromagnet contacts. The proposal relies on the ability to generate spin-polarized triplet pairing by passing an electric current through an NCS. Such an induced triplet pairing bears a similarity to the paradigmatic nonunitary pairing in triplet superfluids with a complex vector order parameter . The qualitative difference is that the induced nonunitary state can be realised in NCSs with a purely real by breaking the time-reversal symmetry in current-biased setups. This offers a possibility to access the unconventional superconductivity in NCSs through electrical transport measurements.